Trio-Based Whole-Exome Sequencing Identifies a De novo EFNB1 Mutation as a Genetic Cause in Female Infant With Brain Anomaly and Developmental Delay - Han, Ji Yoon; Kim, Hyun Jeong; Jang, Ja Hyun; Lee, In Goo; Park, Joonhong (Frontiers in Pediatrics, 2020)
Background: Craniofrontonasal syndrome (CFNS) is a rare, X-linked disorder in which heterozygous females ironically reported the majority of patients and is caused by in the EFNB1 gene located at chromosome Xq13.1. Unlike previous reports, we present a female infant with a de novo EFNB1 missense mutation that demonstrated in clinical diagnosis as global developmental delay (GDD) and brain anomaly without frontonasal dysplasia or other malformation. Case presentation: This study reports the genetic analysis of a 4-month-old female infant presenting brain anomaly and GDD. She was the only child of unrelated parents. Early developmental was characterized by delays in fine motor, achieving gross motor, language, and social-cognitive milestones. She could not control her head hold objects until 4 months of age. Brain resonance imaging (MRI) revealed schizencephaly and dysgenesis of corpus callosum. Trio-based whole exome sequencing revealed a heterozygous c.943C>T (p.Pro315Ser) in the EFNB1. Sanger sequencing confirmed this heterozygous alteration occurring in a dominant de novo manner, as a consequence of phenotypic and genotypic wild-type in both parents. Conclusion: EFNB1 mutation is considered for child with schizencephaly and further study focusing on phenotyping is required to understand the possible contribution of environmental impact and genetic modifier in the expression of EFNB1.